Purchasing power parity between Ecuador and Peru (period 2006-2016) - Orbes Revelo, Belky Nerea (SATHIRI, 2021)
This article analyzed the purchasing power parity (PPP) system which states that the exchange ratesof all currencies worldwide obtaining the same value or “purchasing power”, in one country as well as in another; For this, the merchants have an established law of the PPA so that it is the same in each country and is complied with, however, there are notable differences when comparing it between nations, so the same goods and services cannot be obtained in a State as much as in another, either due to its consumption, availability or quality. Such is the case of Ecuador, which has lost its purchasing power parity within it, due to the events or circumstances that occurred in 2000 such as dollarization, the appreciation of the currency, the fall in the price of oil in the year 2015. Considering the aforementioned points, it will be achieved through a methodology of quantitative approach of a descriptive and explanatory type, to fulfill the development of the objectives of said research, where relevant data such as the consumer price index, exchange rate has been collected and analyzed. , GDP of the two countries under study (Ecuador and Peru). To later finish with the respective conclusions that focus on dollarization; GDP growth and inflationary uncertainty.
Keywords: Purchasing power parity; currency devaluation; dollarization